THE EFFECT OF USING THE DUOLINGO APPLICATION ON SENIOR HIGH SCHOOL STUDENTS’ MASTERY OF GERMAN PERSONALPRONOMEN - Satria Gandrung Muhammad; Soflies M. E. Bingku; Prillimercy E. Kojongian (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The aim of this study is to assess the impact of utilizing the Duolingo application on the comprehension of personal pronouns in the German language among students at SMA 2 Negeri Tondano. The chosen research methodology is a Pre-experimental design known as the One-Group Pretest-Posttest design. Data gathering involves administering pretest-posttest assessments and documenting the outcomes. The collected data will be analyzed using both Descriptive Statistical Analysis and Inferential Statistical Analysis. The findings of the study indicate that hypothesis H1 is accepted, while H0 is rejected, indicating a positive influence of the Duolingo application on students' understanding of personal pronouns in class XI IPS at SMA Negeri 2. This research is anticipated to provide a constructive contribution to educational practitioners by improving the quality of learning through the utilization of the Duolingo application.